Hair cortisol, allostatic load, and depressive symptoms in Australian Aboriginal and Torres Strait Islander people. (4th May 2019) - Berger, Maximus; Taylor, Sean; Harriss, Linton; Campbell, Sandra; Thompson, Fintan; Jones, Samuel; Sushames, Ashleigh; Amminger, G. Paul; Sarnyai, Zoltan; McDermott, Robyn
Abstract: Chronic stress and adversity are associated with poor mental health and are thought to contribute to the existing mental health gap between Aboriginal and Torres Strait Islander people and other Australians. Hair cortisol and allostatic load (AL) are indices of sustained stress and may be mediators of the effects of stress on health. The aim of this study was to examine the relationship between hair cortisol, AL, and depressive symptoms. This cross-sectional study comprised 329 Aboriginal and Torres Strait Islander adolescents and adults recruited at two health screening programs operating in three communities in north Queensland. We measured hair cortisol and calculated an AL index from 10 biomarkers. We assessed depressive symptoms with a version of the Patient Health Questionnaire-9 adapted for Aboriginal and Torres Strait Islander people (aPHQ-9). We found differences in cortisol and AL between the screening programs and communities, which were not explained by depressive symptoms. Overall aPHQ-9 scores were unrelated to hair cortisol ( p  = .25 and p  = .94) and AL ( p  = .30 and p  = .88) when age, gender and smoking were taken into account. However, anhedonia ( p  = .007) and insomnia ( p  = .006) sub-scores were each significantly associated with AL in one study site. Our present data did not demonstrate overall associations of stress biomarkers and multisystem dysregulation with depressive symptoms, which suggests that the relationship between cumulative stress and depression may be better explained by other factors in this population. The specific association between anhedonia and insomnia with AL indicates that chronic multisystem dysregulation plays a role in these features of depression in this population. Lay summary Our study investigated the relationship between symptoms of depression and two biological pathways thought to mediate depression risk – the stress hormone cortisol and allostatic load (AL) – in an Australian Aboriginal and Torres Strait Islander population. Overall, cortisol and AL were unrelated to depression. However, AL was selectively associated with anhedonia (lack of motivation or drive) and sleep disturbances. These results suggest that metabolic dysregulation measured as AL may be relevant to the depression risk in this population.